Identification of a Novel Epigenetic Signature CHFR as a Potential Prognostic Gene Involved in Metastatic Clear Cell Renal Cell Carcinoma - Chen, Xiangling; Lin, Jiatian; Chen, Qiaoling; Liao, Ximian; Wang, Tongyu; Li, Shi; Mao, Longyi; Li, Zesong (Frontiers in Genetics, 2021)
Metastasis is the main cause of clear cell renal cell carcinoma (ccRCC) treatment failure, and the key genes involved in ccRCC metastasis remain largely unknown. We analyzed the ccRCC datasets in The Cancer Genome Atlas database, comparing primary and metastatic ccRCC tumor records in search of tumor metastasis–associated genes, and then carried out overall survival, Cox regression, and receiver operating characteristic (ROC) analyses to obtain potential prognostic markers. Comprehensive bioinformatics analysis was performed to verify that the checkpoint with forkhead associated and ring finger domains (CHFR) gene is a reliable candidate oncogene, which is overexpressed in ccRCC metastatic tumor tissue, and that high expression levels of CHFR indicate a poor prognosis. A detailed analysis of the methylation of CHFR in ccRCC tumors showed that three sites within 200 bp of the transcription initiation site were significantly associated with prognosis and that hypomethylation was associated with increased CHFR gene expression levels. Knockdown of CHFR in ccRCC cells inhibited cell proliferation, colony formation, and migration ability. In summary, our findings suggest that the epigenetic signature on CHFR gene is a novel prognostic feature; furthermore, our findings offer theoretical support for the study of metastasis-related genes in ccRCC and provided new insights for the clinical treatment of the disease.